Investigations of milk-fat lamb production for Western Kansas - Hillman, M.; Menzies, C.; Banbury, Evans E. (Kansas Agricultural Experiment Station, 2011)
150 two-year-old ewes were divided into two groups April 25, 1960, and fed different rations until May 12, or 17 days. One group was given a low-energy ration of 2 pounds of alfalfa hay per ewe per day; the other, a normal ration of 2 pounds alfalfa hay, 3pounds sorghum silage, and ¼ pound whole sorghum grain per ewe per day. May 13 each group was divided into six lots along with 200 yearling ewes.
Keywords: Sheep; Pre-flushing; Performance